DEVELOPMENT OF COMPUTER TECHNOLOGY FOR FORMING AN ACTIVE DICTIONARY FOR LEVEL B1 IN THE REPUBLIC OF UZBEKISTAN (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This research work is dedicated to the development of computer technologies for the formation of B1 level active vocabulary in the conditions of learning the Russian language in the Republic of Uzbekistan. Level B1 is the main level of language learning, in which students have the ability to speak the language on a daily basis and communicate in different situations. The research includes the analysis of students' needs, the development of vocabulary selection criteria, the creation of a database of words and phrases, the development of interactive learning modules and test tasks. In addition, in the Republic of Uzbekistan, attention is paid to adapting technology to the specific characteristics of the educational process, taking into account the cultural and linguistic characteristics of students. The article is an important contribution to the field of education and language teaching in Uzbekistan and can serve as a model for the development of similar educational programs and technologies in other countries with similar educational problems.